2021
DOI: 10.1371/journal.pone.0251759
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tongue–palatal contact during swallowing in patients with skeletal mandibular prognathism after orthognathic surgery

Abstract: This study aimed to evaluate improvement of tongue-palatal contact patterns during swallowing after orthognathic surgery in mandibular prognathism patients. Thirty patients with mandibular prognathism treated by orthognathic surgery (average age of 27 years, 3 months) and 10 controls (average age 29 years, 6 months) participated in this study. Tongue-palatal contact patterns of patients before and three months after surgery were evaluated by electropalatography (EPG) as well as controls. Whole total of tongue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 14 publications
3
12
1
Order By: Relevance
“…Previous reports demonstrated that the tongue-palatal contact pattern during swallowing improved in patients with mandibular prognathism after orthognathic surgery using EPG. 10 Thus, EPG is quite useful for the observation of tongue-palatal contact area during swallowing. However, there is little information focused on tongue-palatal contact changes during swallowing pre and postoperative patients with maxillary protrusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports demonstrated that the tongue-palatal contact pattern during swallowing improved in patients with mandibular prognathism after orthognathic surgery using EPG. 10 Thus, EPG is quite useful for the observation of tongue-palatal contact area during swallowing. However, there is little information focused on tongue-palatal contact changes during swallowing pre and postoperative patients with maxillary protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…To reproduce habitual swallowing, each subject sit on a chair with an upright posture and swallowed water (3 mL, 5 times) for data taking according to the previous study. 10,11 They received instructions to hold the eye-ear plane parallel to the floor. Ten seconds break was given between each swallowing and the motion of swallowing was also recorded by a video camera.…”
Section: Swallowingmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure long-term postoperative stability, it is necessary to examine the stomatognathic functions of patients undergoing orthognathic surgery. Previous studies have reported that surgical orthodontic treatment improves masticatory ability, occlusal force, mandibular condyle and lip movement, and muscle activity [ 7 , 8 , 9 ]. In particular, not only tongue size or tongue habit but also tongue adaptation to changes in the volume of the oral cavity after the orthodontic surgery have been reported to have a great influence on treatment success [ 10 ].…”
Section: Introductionmentioning
confidence: 99%